Significance of mast cell distribution in placental tissue and membranes in spontaneous preterm birth - Needham K; Fadia M; Dahlstrom JE; Harrington K; Shadbolt B; Robson SJ (Dove Medical Press, 2016)
Kate Needham,1 Mitali Fadia,2,3 Jane E Dahlstrom,2,3 Kirsti Harrington,2,3 Bruce Shadbolt,4 Stephen J Robson,1,3,51Department of Obstetrics and Gynaecology, Centenary Hospital for Women and Children, Canberra Hospital, Garran, ACT, Australia; 2Department of Anatomical Pathology, ACT Pathology, Canberra Hospital, Garran, ACT, Australia; 3ANU Medical School, Australian National University, Canberra, ACT, Australia; 4Department of Epidemiology and Population Health, Canberra Hospital, Garran, ACT, Australia; 5John James Medical Centre, Deakin, ACT, Australia Background: Preterm birth is a common cause of adverse neonatal and childhood outcomes, in both the short and long term. Preterm labor is commonly associated with inflammation at the maternal–fetal interface. There is some indirect evidence that mast cells (MCs) might represent a link between hormonal influences and local reactions leading to the onset of labor. Patients and methods: The placentas and membranes of 51 uncomplicated spontaneous term births were compared to those from 50 spontaneous preterm births. Immunohistochemical staining for MC tryptase was undertaken allowing MC concentration, location, and degranulation status to be determined. Regression modeling was used to compare results. Results: There were no significant differences in the demographic characteristics of the two cohorts. There were significantly more MCs in the decidua for term births than preterm births (P=0.03). The presence of histological chorioamnionitis did not affect MC concentrations. Conclusion: Despite evidence suggesting a possible role for MCs in spontaneous preterm birth, this study found that the concentration of decidual MCs was in fact significantly lower in preterm compared to term birth. Keywords: preterm birth, mast cells, inflammation, cohort study, regression modeling